การจัดการความขัดแย้งในการใช้ที่ดินสาธารณประโยชน์ ทุ่งเลี้ยงสัตว์หนองพลับ ตาบลพรุไทย อาเภอบ้านตาขุน จังหวัดสุราษฎร์ธานี - วิชัยดิษฐ, สุจารีย์ (Thai Interdisciplinary and Sustainability Review, 2019)
The purposes of this research were to study the conflict conditions in the utilisation of the public land and the guideline of solving conflicts between the people and the government, and to find the conclusions and solutions to using Nhongplab public land for grazing. The samples of this research were the officials of Pruthai Subdistrict Administrative Organisation and the people who made their living from Nongplap public grazing land of 90 households. The tools used in this study were the questionnaires and analysis of the data in descriptive form. The research findings were summarised as follows: Originally, the Nhongplap public grazing land was an empty land, unoccupied and there was no evidence of any ownership. So, the villagers put the land to agricultural use since B.E. 2495. After that, the Subdistrict Administrative Organisational came to survey the area, reserved an area of 600 acres as a public area, and offered the deeds to use the rest to the villagers. However, it appeared that people in the area refused because they did not want to lose the right to use the land. Everyone wanted the deeds of a piece of land so they gathered to complain through the district to seek out ways to attain the proof of right in said area causing conflicts from then to the present time. The underlying reason behind the conflicts that caused the villager to invade the land was the vagueness of the public, since the area was originally an empty space where residents could occupy the land and that government knew all along but never took any action. Hence, it made the villager protest against the government’s action and it was the duty of government to find the way to resolve said disputes, which might intensify if the government began to make an actual action since people understood that the land was a public space where anyone could use it without any permission issued and some even understood that, if they occupied the land for many years, they could apply for the ownership of the land.